Transformasi Relasi Kuasa dalam Wacana Keagamaan: Analisis Foucaultian atas Dinamika Nahdlatul Ulama dan Penghayat Kepercayaan di Lamongan, Indonesia - Afiah, Amiera Nur; Widianto, Ahmad Arif; Hasanah, Imroatul (Canonia Religia, 2025)
This study analyzes the power relations between Nahdlatul Ulama (NU) as the majority group and the adherents of Sapta Darma as a minority in Lamongan Regency, specifically in Kalitengah Subdistrict, Mungli Village. Using Michel Foucault’s power relations theory, this phenomenological qualitative study examines how NU’s dominant religious discourse, constructed through the Qur’an, hadith, fiqh via Baḥth al-Masā’il, and kitab kuning, functions as an instrument of power to shape the practices and identities of the Sapta Darma community. Data were collected through in-depth interviews with thirteen key informants from both groups and twelve months of field observation. The findings indicate that power relations are productive and relational, in which NU establishes dominant norms that define the boundaries of tolerance, while Sapta Darma adapts socially without relinquishing the core of its beliefs. Foucault’s mechanisms of power are manifested through subtle oversight by NU elites and state institutions, alongside internalization of norms by Sapta Darma, creating self-regulation. The study concludes that social harmony in Mungli is built upon an uneven power structure, where the minority remains vulnerable despite formal recognition. The contribution of this research lies in providing a nuanced understanding of local religious majority-minority power dynamics, offering insights for policymakers and scholars to design inclusive strategies that enhance tolerance and respect for religious diversity.